Helicase-like transcription factor (Hltf) gene-deletion promotes oxidative phosphorylation (OXPHOS) in colorectal tumors of AOM/DSS-treated mice - Helmer, Rebecca A. (PLoS One, 2019)
The helicase-like transcription factor (HLTF) gene—a tumor suppressor in human colorectal cancer (CRC)—is regulated by alternative splicing and promoter hypermethylation. In this study, we used the AOM/DSS-induced mouse model to show Hltf-deletion caused poor survival concomitant with increased tumor multiplicity, and dramatically shifted the topographic distribution of lesions into the rectum. Differential isoform expression analysis revealed both the truncated isoform that lacks a DNA-repair domain and the full length isoform capable of DNA damage repair are present during adenocarcinoma formation in controls. iPathwayGuide identified 51 dynamically regulated genes of 10,967 total genes with measured expression. Oxidative Phosphorylation (Kegg: 00190), the top biological pathway perturbed by Hltf-deletion, resulted from increased transcription of Atp5e, Cox7c, Uqcr11, Ndufa4 and Ndufb6 genes, concomitant with increased endogenous levels of ATP (p = 0.0062). Upregulation of gene expression, as validated with qRT-PCR, accompanied a stable mtDNA/nDNA ratio. This is the first study to show Hltf-deletion in an inflammation-associated CRC model elevates mitochondrial bioenergetics.